Fourth-order elliptic problems involving concave-superlinear nonlinearities - Cavalcante, Thiago R.; Silva, Edcarlos D. (Topological Methods in Nonlinear Analysis, 2022)
The existence of solutions for a huge class of superlinear elliptic problems involving fourth-order elliptic problems defined on bounded domains under Navier boundary conditions is established. To this end we do not apply the well-known Ambrosetti-Rabinowitz condition. Instead, we assume that the nonlinear term is nonquadratic at infinity. Furthermore, the nonlinear term is a concave-superlinear function which can be indefinite in sign. In order to apply variational methods we employ some delicate arguments recovering some kind of compactness.